Lifetime Environmental Impact of Buildings - Méquignon, Marc. (SpringerBriefs in Applied Sciences and Technology, 2014)
This work discusses the impact of the life of buildings on sustainable development methods. The study of the lifespan of the building is used to assess and manage the environmental impacts associated with all the stages of a product's life, from raw material extraction through to repair, maintenance and 'end of life' scenarios. While several papers have discussed the greenhouse gas emissions of buildings, less research has been done on how these are affected by the lifespan of the building. This book serves to highlight the pertinence of this factor and contributes to providing new ideas on efficiency within the life cycle assessment of a structure.